2016
DOI: 10.1021/acs.cgd.6b00566
|View full text |Cite
|
Sign up to set email alerts
|

Guanine Crystallization in Aqueous Solutions Enables Control over Crystal Size and Polymorphism

Abstract: Anhydrous guanine crystals are among the most widespread organic crystals used by organisms to produce structural colors. The main advantage of guanine is its exceptionally high refractive index in the reflecting direction (∼1.8). For the same reason, guanine is a promising candidate material for a variety of different optical applications. Crystallization of guanine is challenging and usually involves using polar aprotic organic solvents such as dimethyl sulfoxide (DMSO). Here, we show that the crystallizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
91
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(101 citation statements)
references
References 54 publications
9
91
1
Order By: Relevance
“…The crystal morphology of the light scattering layer in white spiders (Figure 6a), as well as in other organisms using guanine crystals for light scattering functions, is similar to the theoretical prismatic growth form. [26] It is also similar to the morphology of synthetic crystals grown from aqueous solutions [77] (Figure 7a). The crystals are prisms, with an irregular hexagonal cross-section and typical sizes of 1-2 µm.…”
Section: Biogenic Guanine Morphologiessupporting
confidence: 72%
See 1 more Smart Citation
“…The crystal morphology of the light scattering layer in white spiders (Figure 6a), as well as in other organisms using guanine crystals for light scattering functions, is similar to the theoretical prismatic growth form. [26] It is also similar to the morphology of synthetic crystals grown from aqueous solutions [77] (Figure 7a). The crystals are prisms, with an irregular hexagonal cross-section and typical sizes of 1-2 µm.…”
Section: Biogenic Guanine Morphologiessupporting
confidence: 72%
“…It is conceivable, but not demonstrated that, because the solubility of guanine substantially increases at acidic or basic pH, local control of the pH in the compartment may facilitate transport and concentration at the site of crystallization. [77] A hint of what may well be an additional common crystal building strategy was obtained from the Koi fish scales, where crystals form from an amorphous guanine precursor phase enclosed in spherical vesicles (Figure 8a). [78] Similar vesicles containing apparently solid organic material were observed in silver and white spiders.…”
Section: Control Of Guanine Crystal Morphology and Crystal Formationmentioning
confidence: 99%
“…Because iridophores depend for their iridescence on stacks of membrane-bound reflecting platelets consisting of crystalline guanine 4 , 11 , we first asked whether numbers, sizes, or arrangements of these crystals differ between iridophores found in interstripe versus stripe regions. To visualize guanine crystals in situ required a reagent that would adhere to guanine crystals, and so we screened 12 cell-permeable dyes, chosen for their ability to form both hydrogen bonds and pi-stacking interactions 31 . We found that malachite green efficiently bound guanine and therefore used it to examine guanine crystal organization in iridophores from interstripe versus stripe regions.…”
Section: Resultsmentioning
confidence: 99%
“…An umber of previouss tudies aimed to achieve similarc ontrol of the polymorph and morphology of guanine crystalssyntheticallyi nt he last years. [34][35][36][37][38] Utilizing chitosans ubstrates in the presence of poly(l-glutamic acid), Oaki et al synthesized a thin layer of aggregates of platy AG crystals,w hile it is unclear whether the synthesized AG is a or b phased ue to the low quality of X-ray diffraction patterns. [35] Gur et al demonstrated the polymorph controlb etween GM and AG by controlling the pH in the aqueous environment.…”
mentioning
confidence: 99%
“…[35] Gur et al demonstrated the polymorph controlb etween GM and AG by controlling the pH in the aqueous environment. [34] Kimura et al controlled the morphology of b-AG through the transformation of an amorphous intermediate consisting of guanine sodium salt. [38] Recently,w ed evelopedafacile route that produces nanoplatelets exposing (100) plane with almost pure b phase.…”
mentioning
confidence: 99%